E-Commerce Penjualan Jamu Kelor Berbasis Web Menggunakan Metode Waterfall: Studi Kasus : Kelompok Tani Suka Maju, Desa Atmen - Omenu, Yustina Maria Balok; Yoseph Kelen; Siprianus Septian Manek; Leonard Peter Gelu (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
. Suka Maju Farmer Group in Atmen Village, West Insana District, North Central Timor Regency. The products produced are kelor jehe herbs, moringa temulawak and kelor turmeric, in the process the Suka Maju farmer group always uses the manual method. The problems that often arise are bookkeeping procedures, ordering, entering and exiting goods which are still manual and still use paper for storage. The purpose of this study was to design a web (e-commerce) to provide convenience to consumers in obtaining information about products from the Suka Maju Farmer Group and for the Suka Maju Farmer Group to easily promote Moringa herbal products. The waterfall method is a sequential development model that is systematic and sequential when building software. The process follows the flow of analysis, design, code, testing and maintenance. This research produces an e- commerce website that assists farmer groups in promoting Moringa herbal products and buyers can easily make transactions anytime and anywhere. promote their wares. E-commerce sales of Moringa herbal medicine are built on a website to make it easier for farmer groups like advanced in promoting Moringa herbal products and buyers can easily make transactions anytime and anywhere. At the time of implementation of this system testing was carried out at the research site involving 4 users including as an admin who could process e-commerce selling Moringa herbs and as a buyer who made transactions and as an owner who could confirm transactions and could print reports and as a driver who made deliveries according to the address of the buyer.